TAFSIR AYAT-AYAT PLURALISME AGAMA PERSPEKTIF HUSEIN MUHAMMAD - Siti Hajar; Umayah Umayah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This paper aims to show Husein Muhammad's interpretation on verses related to religious pluralism. To achieve that purpose, the author uses the hermeneutic method of liberation by Farid Esack which wants to show the relationship between the text of the Qur’an and the context of the relationship between religious believers, which will then build justice based on human values. The key to Farid Esack's hermeneutics relates to piety, monotheism, relationships between humans, the oppressed, justice and concrete practices as a form of struggle (jihad) to humanize humans. The conclusion of this paper shows that Husein Muhammad has a very tolerant, wise and full of wisdom in conveying the meaning of religious pluralism verses. He believes that the messages in the Qur’an act as a guide to uphold human values. So that, the verse of religious pluralism requires for an equal position of religious people as God's creatures. There is no justification for certain religious communities which is the most right or which is clearly wrong.Keywords: Religious Pluralism, Husein Muhammad. Tulisan ini bertujuan untuk memperlihatkan penafsiran Husein Muhammad atas ayat-ayat yang terkait dengan tema pluralisme agama. Untuk mencapai tujuan tersebut, penulis menggunakan metode hermeneutika pembebasan Farid Esack yang ingin memperlihatkan relasi antara teks Alquran dengan konteks hubungan antarumat beragama, yang kemudian akan membangun keadilan berdasarkan nilai-nilai kemanusiaan. Kunci hermeneutika Farid Esack berkaitan dengan takwa, tauhid, hubungan antarsesama manusia, golongan yang tertindas, keadilan serta praktik konkret sebagai bentuk perjuangan (jihad) memanusiakan manusia. Kesimpulan dari tulisan ini menunjukkan bahwa Husein Muhammad memiliki pandangan yang amat toleran, bijak dan penuh hikmah dalam menyampaikan makna atas ayat-ayat pluralisme agama. Ia meyakini bahwa pesan-pesan dalam Alquran berperan sebagai pembawa petunjuk untuk menjunjung tinggi nilai-nilai kemanusiaan. Sehingga, ayat pluralisme agama menghendaki adanya kesamaan kedudukan umat beragama sebagai makhluk Tuhan. Tidak ada justifikasi atas umat agama tertentu yang paling benar atau yang jelas salah.Kata Kunci: Pluralisme agama, Husein Muhammad.